Feasibility of Comparing the Results of Pancreatic Resections between Surgeons: A Systematic Review and Meta-Analysis of Pancreatic Resections. (17th August 2015) - Gurusamy, Kurinchi; Toon, Clare; Virendrakumar, Bhavisha; Morris, Steve; Davidson, Brian
Abstract : Background. Indicators of operative outcomes could be used to identify underperforming surgeons for support and training. The feasibility of identifying HPB surgeons with poor operative performance ("outliers") based on the results of pancreatic resections is not known. Methods. A systematic review of Medline, Embase, and the Cochrane library was performed to identify studies on pancreatic resection including at least 100 patients and published between 2004 and 2014. Proportions that lay outside the upper 95% and 99.8% confidence intervals based on results of the systematic reviews were considered as "outliers." Results. In total, 30 studies reporting on 10712 patients were eligible for inclusion in this review. The average short-term mortality after pancreatic resections was 3.1% and proportion of patients with procedure-related complications was 47.0%. None of the classification systems assessed the long-term impact of the complications on patients. The surgeon-specific mortality should be 5 times the average mortality before he or she can be identified as an outlier with 0.1% false positive rate if he or she performs 50 surgeries a year. Conclusions. A valid risk prognostic model and a classification system of surgical complications are necessary before meaningful comparisons of the operative performance between pancreatic surgeons can be made.